Synthesis of Schiff Base Compound from Vanillin and p-Toluidine by Solvent Free-Mechanochemical Method - Hasanah, Ulfatul; Hanapi, Ahmad; Ningsih, Rachmawati (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.609, 2017)
Synthesis processes by solvent free or known as greeen method  are widely used and developed compared to conventional method based on solution. This research has successfully synthesized Schiff base compound 2-methoxy-4-(( p -tolylimino)methyl)phenol from vanillin dan p -toluidineby solvent free-mechanochemical method. Each of reactans with molar ratio 1:1 was grinded using mortar and pastle with variation of time grinding while 10, 15, dan 20 minutesand characterized the moleculer structure by spectrophotometric technique. Synthesis process was produce excellent result with high yield and purities. Synthesis products are pale yellow solid and slightly soluble in water. UV-Vis spectrum have optimum absorption on 329 and 285 nm,while FTIR spectra shows that each of product have charateristic bond C=N on 1585,532 - 1590,203 cm -1 . Analysis using GC-MS shows target compound has molecular ion on m/z 241 that indicated weight of Schiff base compound.